Ras initiates phosphatidyl-inositol-3-kinase (PI3K)/PKB mediated signalling pathways in untransformed human peripheral blood T lymphocytes - Samstag, Yvonne; Nebl, Gabriele (Advances in enzyme regulation, 2005)
Activation of T lymphocytes through costimulation of the T cell receptor/CD3 complex (TCR/CD3) and coreceptors (e.g. CD2 or CD28) leads to production of the growth factor interleukin-2 (IL-2) and subsequent proliferation. For these activation processes, remodelling of the actin cytoskeleton plays an important functional role. We have shown that the activity of the actin-remodelling protein cofilin is crucially involved in T lymphocyte activation processes. In unstimulated human peripheral blood T lymphocytes (PB-T) cofilin exists in its inactive ser-3-phosphorylated form. T lymphocyte activation through costimulation of TCR plus the coreceptors CD28 or CD2, respectively, induces the dephosphorylation of cofilin. Concomitantly, cofilin associates with the actin cytoskeleton. The functional importance of cofilin for T lymphocyte activation was shown employing cell permeable peptides which block binding of cofilin to actin. In human PB-T these peptides impair the formation of the immunological synapse and inhibit the induction of T lymphocyte proliferation and cytokine production. The serine phosphatases PP1 and PP2A dephosphorylate cofilin in T lymphocytes. Importantly, a PKC-Ras-MEK/PI3K-cascade links costimulation of PB-T through TCR/CD3 and CD28 to activation of cofilin through dephosphorylation. Notably, the induction of cofilin dephosphorylation requires the combined activities of two Ras-effectors, namely MEK and PI3K. With respect to PI3K, this result was unexpected since so far it was generally assumed that-unlike in other cell types-Ras is not able to activate PI3K in T lymphocytes, as concluded from experiments performed with the human T-lymphoma line Jurkat. This discrepancy implied that the signalling events upstream of PI3K differ between PB-T and Jurkat cells. In line with this, we found that in PB-T the PI3K-inhibitors wortmannin and LY294002 block activation induced cofilin dephosphorylation and its association with the actin cytoskeleton. In Jurkat cells, however, where cofilin is present mainly in its non-phosphorylated form and permanently associated with the actin cytoskeleton, wortmannin and LY294002 do not block these events. Studies by others employing these PI3K-inhibitors have also led to such contradictory results: While in stimulated PB-T these inhibitors repress expression of IL-2, they even enhance IL-2 expression in Jurkat cells. These findings show that signalling events in Jurkat cells are not representative for signalling processes in untransformed human T lymphocytes. Importantly, our data demonstrate that-rebutting a persistent dogma-a T-cell specific uncoupling of PI3K from Ras does not exist.
Gesehen am 16.07.2021